Cover Feature: Atomically Dispersed Copper on N‐Doped Carbon Nanosheets for Electrocatalytic Synthesis of Carbamates from CO2 as a C1 Source (ChemSusChem 9/2021). Issue 9 (14th April 2021) - Li, Shi‐Ming; Shi, Yi; Zhang, Jing‐Jie; Wang, Ying; Wang, Huan; Lu, Jia‐Xing
Abstract : The Cover Feature shows an atomically dispersed Cu species on N‐doped carbon nanosheet composite material for electrocatalytic synthesis of carbamates using CO2 under mild conditions. The electrocatalyst has good durability and universal applicability. More information can be found in the Full Paper by S.‐M. Li et al .